Penerapan Posisi Head Up 30 Derajat Terhadap Pencegahan TIK Pasien Cedera Kepala di Ruang IGD RSUD PROF. DR. H. Aloei Saboe Kota Gorontalo - Pipin Yunus; Arifin Umar; Susanti Monoarfa; Rahmawaty Dali (Malahayati Nursing Journal, 2024)
ABSTRACT Head injury is a traumatic disturbance of brain function accompanied or without interstitial bleeding which includes trauma to the scalp, skull and brain. Complications that occur in head injuries are increased intracranial pressure, namely the pressure that occurs in the cerebral space due to an increase in brain volume that exceeds the tolerance threshold in the cranial space. Head injury treatment can be done by controlling intracranial pressure. Surgical intervention by providing a 30 degree head position can be given to head injury patients. The aim of the research is to analyze the 30 degree head up position on the prevention of ICT. The research method used pre-experimental design with one group pre and post test. The sample in this study consisted of 10 respondents. The results of the research showed that the highest pre-intervention intracranial pressure was obtained by GCS, namely Mild Head Injury, 5 respondents, the highest blood pressure, namely Stage 1 Hypertension, 4 respondents, the highest pulse category, namely bradycardia, 5 respondents, and the highest pain scale, namely mild, 5 respondents. Meanwhile, post-intervention intracranial pressure experienced the most changes obtained for GCS, namely Mild Head Injury, 7 respondents, the highest blood pressure, namely Pre Hypertension, 5 respondents, the highest pulse category, namely normal pulse, 5 respondents, and the lightest pain scale, namely 6 respondents. Based on the results of parametric and non-parametric statistics, it was found that all components of intracranial pressure had an influence after intervention, namely GCS with a p-value of 0.003, blood pressure with a p-value of 0.000, pulse with a p-value of 0.001, headache with a p-value of 0.000 where 0.05, which means it has a significant effect after being given the intervention. For this reason, applying a 30 degree head up position can increase blood supply to the brain thereby reducing the risk of increasing intracranial pressure due to thrombolytic stroke as well as clinical complications for the patient. Keywords: Head Injury, Head Up 30 Degrees, ICT  ABSTRAK Cedera kepala adalah gangguan traumatik dari fungsi otak yang disertai atau tanpa perdarahan intersisial yang meliputi trauma kulit kepala, tengkorak, dan otak. Komplikasi yang terjadi pada cedera kepala adalah peningkatan tekanan intrakranial, yaitu tekanan yang terjadi pada ruang serebral akibat bertambahnya volume otak melebihi ambang toleransi dalam ruang cranium. Perawatan cedera kepala dapat dilakukan dengan mengontrol tekanan intrakranial. Intervensi keperawatan dengan memberikan posisi kepala 30 derajat dapat diberikan pada pasien cedera kepala. Tujuan penelitian yaitu untuk menganalisis posisi head up 30 derajat terhadap pencegahan TIK. Metode penelitian menggunakan pre-experimental dengan desain one grup pre dan post test. Sampel pada penelitian ini berjumlah 10 respoden. Hasil penelitian menunjukkan tekanan intrakranial pre intervensi didapatkan untuk GCS terbanyak yaitu Cedera Kepala Ringan sebanyak 5 responden, tekanan darah terbanyak yaitu Hipertensi Tahap 1 sebanyak 4 responden, kategori nadi terbanyak yaitu nadi bradikardi sebanyak 5  responden, serta skala nyeri terbanyak yaitu ringan sebanyak 5 responden. Sedangkan tekanan intrakranial post intervensi mengalami perubahan didapatkan untuk GCS terbanyak yaitu Cedera Kepala Ringan sebanyak 7 responden, tekanan darah terbanyak yaitu Pre Hipertensi sebanyak 5 responden, kategori nadi terbanyak yaitu nadi normal sebanyak 5  responden, serta skala nyeri terbanyak yaitu ringan sebanyak 6 responden. Berdasarkan hasil statistik parametrik dan non parametrik didapatkan bahwa semua komponen tekanan intrakranial memiliki pengaruh setelah dilakukan intervensi yaitu GCS dengan p-value 0,003, tekanan darah dengan p-value 0,000, nadi dengan p-value 0,001, nyeri kepala dengan p-value 0,000 dimana 0,05 yang artinya memiliki pengaruh secara signifikan setelah diberikan intervensi. Untuk itu pada penerapan posisi head up 30 derajat dapat meningkatkan suplay darah ke otak sehingga menurunkan resiko peningkatan tekanan intracranial akibat stroke trombolitik maupun komplikasi klinis pasien. Kata Kunci: Cedera Kepala, Head Up 30 Derajat, TIK